ANALYSIS OF ACTOR RELATIONS IN FLOOD DISASTER MANAGEMENT EFFORTS IN DENPASAR CITY IN 2025 - Ni Komang Ayu Agustini; Lilik Antarini; Nyoman Sumawidayani (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2026)
Flood disaster management requires the active involvement of multiple actors because disaster problems cannot be effectively addressed by a single institution. This study aims to analyze actor relations in flood disaster management efforts in Denpasar City in 2025. The study employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation. Informants were selected using purposive sampling and consisted of 11 individuals representing government institutions, village government, private sector institutions, academics, and flood-affected communities. Data were analyzed using the interactive model of Miles and Huberman and interpreted through the actor analysis framework of Mendel and Brinkerhoff, which includes actor identification, interests, resources, relations and interactions, and actor strategies. The findings indicate that flood disaster management in Denpasar City involved seven main actors, namely BPBD Denpasar City, PUPR Denpasar City, Pemecutan Village Government, Aqua Bali Factory, Denpasar Industrial Training Center, academics from Universitas Warmadewa, and local communities. Their relations were characterized by coordination, collaboration, and interdependence in emergency response, infrastructure repair, logistical support, policy input, and community participation. The study concludes that actor relations in Denpasar City flood disaster management were effective, participatory, and sustainable because each actor performed complementary roles supported by shared objectives and available resources.